Tenacic Acids: A New Class of Tenacious Binders to Metal Oxide Surfaces. Issue 55 (6th September 2018) - Komati, Rajesh; Mitchell, Carl A.; LeBeaud, Anastasia; Do, Huy; Goloverda, Galina Z.; Kolesnichenko, Vladimir L.
Abstract: The backbone of 2‐hydroxyisophthalic acid was identified as a potential metal oxide anchor because of the perfect alignment of all three of its donor groups for binding to inorganic surfaces. It can therefore be used in the design of organic linkers for metal oxide based hybrid materials. Optimized and scalable methods for the synthesis of 2‐hydroxyisophthalic acid (1 ) and its 5‐substituted derivatives: 5‐bromo‐ (2 ), 5‐sulfooxy‐ (3 ), 5‐hydroxy‐ (4 ), and 5‐PEG600 (5 ) are presented. Dynamic light scattering (DLS) demonstrated that compound2 inhibits Fe(OH)3 precipitation when Fe III aqueous solutions are titrated with NaOH, while similar titrations in the presence of the structurally‐related isophthalic and salicylic acids, both missing the third donor group, show turbidity at pHs as low as 2.3 and 3.5, respectively. The adduct synthesized from 4.5 nm γ‐Fe2 O3 nanoparticles and5 is water‐, alcohol‐ and CH2 Cl2 ‐soluble, and forms stable aqueous colloids in the pH range of 4.4–8.7. Moreover, at a pH close to neutral these colloids survive at 100 °C, demonstrating the high practicality of 2‐hydroxyisophthalic acid for nanoparticulate inorganic/organic hybrid material design. Abstract : The synergistic effect of the three donor groups in 2‐hydroxyisophthalic acid secures its strong covalent binding to metal oxide surfaces. Its ability to form stable adducts with iron oxide at a wide range of pHs has been demonstated, which leads to a drastic improvement of its practicality in functional hybrid material design.